ANALISA KEBUTUHAN DAN KETERSEDIAAN AIR BERSIH DI UNIT PDAM KECAMATAN WONOSALAM - Mahendra, Andyka Zulfa; Kurniawan, Fernando Dwi; Rizani, Mohammad Debby; Yudaningrum, Farida (Universitas PGRI Semarang, 2025)
The need for clean water in Wonosalam District increases every year as seen from data from the Demak Regency Central Statistics Agency, where the population of Wonosalam District from 2018 to 2022 has increased, so the need for water is also increasing. Therefore, the aim of this research is to determine water needs, water availability, quantity and quality of water and determine the capacity of the reservoir to accommodate clean water. Starting with collecting secondary data, namely population data, data on the number of PDAM customers, source capacity and discharge data, water quality samples. In calculating population growth, population data for the last 5 years is used with predicted calculations until 2032. To calculate this data, the Geometry method, Arithmetic method, and Linear Regression method are used. Then from these calculations, the Arithmetic method was chosen because it has a smaller value. Based on data calculations using the arithmetic method, the value of clean water needs from the population calculation in 2031 is 149,251 liters/second. Meanwhile, the need for clean water for the number of PDAM customers in 2032 is 7,176 liters/second. For the availability of clean water from a source capacity of 10 liters/second and a production discharge of 7,176 liters/second.